Fly ash artificial aggregate - Khoo, Hooi Chin (Macao Innnovation & Invention Association, 2014)
Macau International Innovation & Invention Expo 2013 (IIEX), 28th June - 30th June 2013 organized by Macao Innnovation & Invention Association at Macau Fisherman Wharf Exhibition Centre, China.